2019
DOI: 10.1101/774026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Free Energy Principle in Human Postural Control System: Skin Stretch Feedback Reduces the Entropy

Abstract: Human upright standing involves an integration of multiple sensory inputs such as vision, vestibular and somatosensory systems. It has been known that sensory deficits worsen the standing balance. However, how the modulation of sensory information contributes to postural stabilization still remains an open question for researchers. The purpose of this work was to formulate the human standing postural control system in the framework of the free-energy principle, and to investigate the efficacy of the skin stret… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…It has the characteristics of low density and indentation thresholds, compared to FA-I and SA-I type mechanoreceptors on the hand [10]. Due to its nature of the less sensitive spatial resolution, relatively fewer haptic devices utilized the skin-stretch feedback to provide the tactile information to the hand [11]- [14]. Recently, we applied the skin-stretch feedback to the dorsum of a hand during the virtual object grasping task and demonstrated that the skin-stretch feedback could modulate the perceived size of an object [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has the characteristics of low density and indentation thresholds, compared to FA-I and SA-I type mechanoreceptors on the hand [10]. Due to its nature of the less sensitive spatial resolution, relatively fewer haptic devices utilized the skin-stretch feedback to provide the tactile information to the hand [11]- [14]. Recently, we applied the skin-stretch feedback to the dorsum of a hand during the virtual object grasping task and demonstrated that the skin-stretch feedback could modulate the perceived size of an object [15].…”
Section: Introductionmentioning
confidence: 99%